MATTHEAN ATONEMENT RITUALS - M Nel (Acta Theologica)
This article focuses on rituals in the Gospel of Matthew that affect forgiveness between God and human beings, as well as between human agents. It argues that rituals play an important role in signalling and affecting forgiveness. It gives an operational definition of a ritual and identifies possible atonement rituals in the Gospel of Matthew up to the crucifixion of Jesus. These rituals are analysed to determine how they affect atonement through the forgiveness of sins. Since access to these rituals is only possible through the text of Matthew, Strecker’s taxonomy of how rites and text are interwoven in the New Testament is used to order the analysis of Matthew. Finally, concluding remarks are made on the relationship between ritual and authority in Matthew.